PENYULUHAN OBAT GENERIK, OBAT YANG TERJANGKAU DAN EFEKTIF UNTUK PERAWATAN KESEHATAN MASYARAKAT - Lilis Tuslinah; Miqdad Nurabdullah Al Anshari; Ilham Nurfadilah Asopari; Childa Syundari; Naufal Sauqi (LPPM Universitas Abdurrab, 2023)
Cilacap Regency, located in Central Java Province, is a region with a significant population. However, the community's understanding of the safety, quality and effectiveness of generic medicines still needs improvement. To address this issue, a counseling activity on generic medicines was held specifically for the heads of RT and RW in Tarisi Village. The purpose of this activity was to provide participants with an understanding of the benefits, quality, and affordable price of generic drugs as an effective alternative in health care. The method applied in this extension activity involved lectures, with the evaluation of extension results analyzed using statistics using the Paired Sample T Test method. The results of data analysis through the Paired Samples T Test method indicated that the Sig. (2-tailed) was 0.000 (<0.05), indicating an increase in participants' understanding and knowledge after the extension activities were carried out. With this counseling, participants managed to gain better knowledge about generic drugs, including their benefits, quality, and more affordable prices compared to branded and patented drugs.